TECHNOLOGICAL ASSURANCE OF MECHANICAL PROCESSING OF COMPLEX SHAPED PARTS BASED ON MACHINING CENTERS WITH NUMERICAL CONTROL - BÎCIOC, Mihail (Journal of Engineering Science (Chişinău))
To achieve high precision in the machining of complex-shaped parts, the correct combination of technologies with the machining center is necessary, especially if it has only 3 axes, to obtain the best results. The present study focuses on technological assurance of the mechanical processing of complex-shaped parts on Computer Numerical Control (CNC) machining centers. The study proposes a methodology for optimizing the machining process by implementing appropriate technological measures, such as tool selection, cutting parameters, and cost-effective process planning. The proposed methodology aims to enhance the quality and productivity of the machining process while minimizing the production time and cost. The results of the study demonstrate the effectiveness of the proposed methodology in improving the machining performance and achieving the desired product quality.